Hemodynamic, Thyroid and Immunomodulatory Effects of Heroin in Rats - Maulood, Ismail M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Diacetylmorphine (heroin) has many effects on the body system; it exerts effects on cardiovascular, immune and endocrine systems. The aim of the this study is to investigate the short-term effects of low and high doses of heroin on systolic blood pressure (SBP), thyroid hormones and monocyte chemoattractant protein-1 (MCP-1). The experimental rats were divided into three groups, each with six individuals and the treatments were continued for seven days.  SBP significantly reduced by heroin administration in the second dose as compared with the control group.   A marked decrease in the serum NO level was also noticed after first (low) and second (high) dose of administration as compared with control group.  The present results also revealed that serum MCP-1 was statistically increased in the second dose of heroin group. Statistical analysis showed that both serum T3 and T4 levels were reduced significantly by heroin administration. In conclusions, for the first time, our findings suggested that diacetylmorphine could affect immune system through MCP-1 elevation. As well as heroin may affect cardiac and liver functions via increasing troponin-T and bilirubin levels.